Chen Ning “Frank” Yang (1922–2025): Profound proponent of symmetry - Stephen L. Adler (Proceedings of the National Academy of Sciences, 2026)
Chen Ning Yang made important contributions to the theory of solvable models in statistical mechanics, including generalizations of the Bethe Ansatz, magnetization in the Ising model, the Lee-Yang circle theorem, and the Yang-Baxter equation. Most famously, Yang made transformative contributions to the current Standard Model of elementary particle interactions. The proposal of Yang and T. D. Lee, that left–right symmetry (parity) is violated in weak particle decays, established that the primary currents involved in weak interactions are left handed. The work of Yang and R. L. Mills gave a framework for force carriers coupling to these currents that are non-Abelian generalizations of the electromagnetic photon, which unlike the electrically neutral photon, carry “charges” to which they self-couple. Two decades of work by others on quantization and mass generation mechanisms then culminated in the Standard Model.